Globalisation, neoliberalisation, and network governance: an international study of outsourcing in health and physical education. Issue 2 (3rd March 2020) - Macdonald, Doune; Johnson, Rebecca; Lingard, Bob
ABSTRACT: Led by an Australian team who witnessed the proliferation of local and global private companies, foundations and semi-government services seeking to 'partner' with schools, this special issue seeks to unpack global patterns in the 'outsourcing' of curricula. More specifically, using the 'problems' of obesity and mental health, the project aims to understand: the rationales and experiences of schools and teachers with external providers; factors that influence the appeal and opportunities for external providers; the nature, extent and effects of networks that exist between external providers and other agencies; and the intellectual authorities that external providers use to frame their products and services. Theoretically, we draw on the concepts of neoliberalisation, networks and governance, and Bernstein's message systems, the latter providing a framework to understand how curricula are shaped by agents and agencies whose remits lie outside the traditional education message systems.